The cellist [large type] : a novel - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series, 2021)
After the poisoning of a Russian billionaire, Gabriel Allon travels across Europe and finds himself in the reach of a virtuoso cellist who may be able to help uncover the truth about his friend's death.